High-performance low-cost silicon nitride-based ceramic substrate and manufacturing method thereof
By mixing low-cost and high-performance silicon nitride raw materials in silicon nitride-based ceramic substrates and adopting specific processes, the problem of high production costs of existing silicon nitride-based ceramic substrates is solved, and a high-performance and low-cost silicon nitride-based ceramic substrate is realized, with excellent thermal conductivity, mechanical strength and fracture toughness.
Patent Information
- Application Number
- CN202411959915.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-11
AI Technical Summary
While maintaining high performance, existing silicon nitride-based ceramic substrates have high production costs, resulting in insufficient competitiveness in application fields with high cost sensitivity.
By mixing low-cost silicon nitride and high-performance silicon nitride raw materials, combining Y2O3, MgO, butyl acetate, dispersant and prefabricated adhesive, a silicon nitride-based ceramic substrate with excellent thermal conductivity, mechanical strength and fracture toughness were prepared using specific ball milling and heat treatment processes.
A high-performance, low-cost silicon nitride-based ceramic substrate is realized, with thermal conductivity reaching above 65W/m·K, mechanical strength and fracture toughness reaching above 650MPa and above 6.0MPa·m1/2, providing higher performance and lower manufacturing costs than existing ZTA substrates.
Smart Images

Figure BDA0005216844810000051 
Figure BDA0005216844810000061
Abstract
Description
Technical Field
[0001] The invention relates to the field of manufacturing silicon nitride-based ceramic substrates, and in particular to a high-performance and low-cost silicon nitride-based ceramic substrate and a manufacturing method thereof. Background Art
[0002] Silicon nitride substrate is a ceramic substrate with excellent conductivity and strength, and has the characteristic of maintaining stable physical properties at high temperatures. This leads to its use in a variety of applications such as electronic devices, power semiconductor modules, LEDs, and automotive parts.
[0003] Silicon nitride substrates have high thermal conductivity (above 80W / m·K), excellent mechanical strength (above 700MPa), high fracture toughness (above 6.0MPa.m1 / 2), excellent heat resistance and wear resistance, and are suitable for applications requiring high reliability. However, in order to maintain high performance, high-purity raw materials and complex manufacturing processes are required. In addition, high-priced raw materials and sintering processes lead to high production costs, which will reduce competitiveness in cost-sensitive application fields due to low economic efficiency.
[0004] Secondly, it also includes ZTA substrates, which have relatively low manufacturing costs, moderate mechanical strength and heat resistance. They are widely used in low- and medium-end applications and can be used as an economical solution in mass-produced products that do not require high performance. However, their thermal conductivity is relatively low (20-30W / m·K), their fracture toughness is low (2.0-3.0MPa.m1 / 2), and their mechanical strength is lower than that of silicon nitride substrates (600-700MPa level), so they are not suitable for high-performance electronic devices or high-reliability components.
[0005] Therefore, it is necessary to propose a high-performance, low-cost silicon nitride-based ceramic substrate and a manufacturing method thereof to solve the above problems. Summary of the invention
[0006] The main purpose of the present invention is to provide a high-performance and low-cost silicon nitride-based ceramic substrate and a manufacturing method thereof, which can effectively solve the problems in the background technology.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] A high-performance, low-cost silicon nitride-based ceramic substrate comprises a low-cost silicon nitride raw material, a high-performance silicon nitride raw material, Y2O3, MgO, butyl acetate, a dispersant, and a prefabricated adhesive. The low-cost silicon nitride raw material is a powder with a particle size of 1-3 μm; the high-performance silicon nitride raw material is a powder with a particle size of 0.7 μm. Al≤200ppm, Fe≤100ppm, and Ca≤50ppm are contained in the low-cost silicon nitride raw material and the high-performance silicon nitride raw material.
[0009] Preferably, the low-cost silicon nitride raw material is 50wt%; the high-performance silicon nitride raw material is 50wt%; Y2O3 is 2mol%; MgO is 5mol%; butyl acetate is 60wt% of the total amount of the low-cost silicon nitride raw material and the high-performance silicon nitride raw material; the dispersant is 0.5wt%; the prefabricated adhesive includes 70wt% of butyl acetate and 30wt% of resin mixed, and the weight percentage of the prefabricated adhesive is 10-25wt% of the total amount of the low-cost silicon nitride raw material and the high-performance silicon nitride raw material.
[0010] A method for manufacturing a high-performance and low-cost silicon nitride-based ceramic substrate comprises the following steps:
[0011] S1: Raw material preparation and quality management, prepare low-cost silicon nitride raw materials, high-performance silicon nitride raw materials, Y2O3, MgO, butyl acetate, dispersant, prefabricated adhesive. The prefabricated adhesive is in a gel state with a viscosity of 30,000 cps. Test the Al, Fe, and Ca in the low-cost silicon nitride raw materials and high-performance silicon nitride raw materials. When they meet the requirements of Al≤200ppm, Fe≤100ppm, and Ca≤50ppm, they can be used;
[0012] S2: Slurry preparation: low-cost silicon nitride raw material, high-performance silicon nitride raw material, Y2O3, MgO, butyl acetate, dispersant, and prefabricated adhesive are ball-milled for 10 hours using 10 mm silicon nitride balls. After the first ball-milling, they are ball-milled for 10 hours using 10 mm silicon nitride balls. After mixing, impurities are removed by a 10000 gaus magnetic filter and a 10 μm ink cartridge filter. Then, the mixture is treated with a vacuum degasser for 30 minutes to remove residual bubbles, thereby making a slurry.
[0013] S3: Molding and inorganic coating: prepare a PET film, and mold the slurry into a thickness of 0.40 mm on one side of the PET film through a casting process. Cut the molded substrate into a size of 170 mm × 230 mm, and evenly coat BN on the opposite side of the PET film by spray coating, wherein the BN coating thickness is 5-10 μm, thereby completing the molded substrate;
[0014] S4: heat treatment, including degreasing: the formed substrate is heated to 250°C at 5°C / min in a nitrogen atmosphere and maintained for one hour. After the temperature is maintained, the temperature is increased to 500°C at 2°C / min and maintained for 2 hours, and then the temperature is increased to 1000°C at 3°C / min and maintained for 1 hour.
[0015] Sintering: The degreased substrate is kept at 1900°C for 3 hours in a sintering furnace under nitrogen pressure of 9 bar. After the holding period, it is naturally cooled to 1500°C at 9 bar and then forcedly cooled using a high-speed fan.
[0016] S5: Post-processing: wet grinding of the sintered substrate to remove BN particles remaining on the substrate surface and improve the surface roughness to less than 10um;
[0017] S6: Test the post-processed substrate, including thermal conductivity, mechanical strength, fracture toughness, and microstructure. The thermal conductivity is measured by the hot wire method, and the measurement result is above 65W / m·K; the mechanical strength is measured by three-point bending, and the measurement result is above 650MPa; the fracture toughness is measured by the single-side pre-crack method of ASTMC1421, and the measurement result is ≥6.0MPa·m 1 / 2 The microstructure was analyzed by SEM, which confirmed that the substrate had a uniform particle size distribution of 0.5 to 2 μm and a porosity of ≤1%.
[0018] Compared with the prior art, the present invention provides a high-performance and low-cost silicon nitride-based ceramic substrate and a manufacturing method thereof, which has the following beneficial effects:
[0019] The high-performance and low-cost silicon nitride-based ceramic substrate and its manufacturing method provide an optimal particle size distribution by mixing low-cost silicon nitride and high-performance silicon nitride, thereby reducing the manufacturing cost and providing a thermal conductivity of more than 65W / mK, a strength of more than 650MPa, and a fracture toughness of 6.0MPa·m 1 / 2 The above physical properties provide thermal conductivity more than 2 times higher than that of existing ZTA substrates and fracture toughness more than 85%. In addition, during the sintering process, nitrogen pressurization and inorganic coating prevent the substrate from cracking and form a uniform microstructure. This substrate provides a highly reliable and economical alternative for high-performance power semiconductors, LED substrates and consumer electronic devices. DETAILED DESCRIPTION
[0020] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.
[0021] Embodiment 1:
[0022] A high-performance and low-cost silicon nitride-based ceramic substrate, comprising a low-cost silicon nitride raw material, a high-performance silicon nitride raw material, Y2O3, MgO, butyl acetate, a dispersant, and a prefabricated adhesive, wherein the low-cost silicon nitride raw material has a powder with a particle size of 1-3 μm; the high-performance silicon nitride raw material has a powder with a particle size of 0.7 μm, and Al≤200ppm, Fe≤100ppm, and Ca≤50ppm in the low-cost silicon nitride raw material and the high-performance silicon nitride raw material;
[0023] The low-cost silicon nitride raw material is 50wt%; the high-performance silicon nitride raw material is 50wt%; Y2O3 is 2mol%; MgO is 5mol%; butyl acetate is 60wt% of the total amount of the low-cost silicon nitride raw material and the high-performance silicon nitride raw material; the dispersant is 0.5wt%; the prefabricated adhesive includes 70wt% of butyl acetate and 30wt% of resin, and the weight percentage of the prefabricated adhesive is 10-25wt% of the total amount of the low-cost silicon nitride raw material and the high-performance silicon nitride raw material.
[0024] A method for manufacturing a high-performance and low-cost silicon nitride-based ceramic substrate comprises the following steps:
[0025] S1: Raw material preparation and quality management, prepare low-cost silicon nitride raw materials, high-performance silicon nitride raw materials, Y2O3, MgO, butyl acetate, dispersant, prefabricated adhesive. The prefabricated adhesive is in a gel state with a viscosity of 30,000 cps. Test the Al, Fe, and Ca in the low-cost silicon nitride raw materials and high-performance silicon nitride raw materials. When they meet the requirements of Al≤200ppm, Fe≤100ppm, and Ca≤50ppm, they can be used;
[0026] S2: Slurry preparation: low-cost silicon nitride raw material, high-performance silicon nitride raw material, Y2O3, MgO, butyl acetate, dispersant, and prefabricated adhesive are ball-milled for 10 hours using 10 mm silicon nitride balls. After the first ball-milling, they are ball-milled for 10 hours using 10 mm silicon nitride balls. After mixing, impurities are removed by a 10000 gaus magnetic filter and a 10 μm ink cartridge filter. Then, the mixture is treated with a vacuum degasser for 30 minutes to remove residual bubbles, thereby making a slurry.
[0027] S3: Molding and inorganic coating: prepare a PET film, and mold the slurry into a thickness of 0.40 mm on one side of the PET film through a casting process. Cut the molded substrate into a size of 170 mm × 230 mm, and evenly coat BN on the opposite side of the PET film by spray coating, wherein the BN coating thickness is 5-10 μm, thereby completing the molded substrate;
[0028] S4: heat treatment, including degreasing: the formed substrate is heated to 250°C at 5°C / min in a nitrogen atmosphere and maintained for one hour. After the temperature is maintained, the temperature is increased to 500°C at 2°C / min and maintained for 2 hours, and then the temperature is increased to 1000°C at 3°C / min and maintained for 1 hour.
[0029] Sintering: The degreased substrate is kept at 1900°C for 3 hours in a sintering furnace under nitrogen pressure of 9 bar. After the holding period, it is naturally cooled to 1500°C at 9 bar and then forcedly cooled using a high-speed fan.
[0030] S5: Post-processing: wet grinding of the sintered substrate to remove BN particles remaining on the substrate surface and improve the surface roughness to less than 10um;
[0031] S6: Test the post-processed substrate, including thermal conductivity, mechanical strength, fracture toughness, and microstructure. The thermal conductivity is measured by the hot wire method, and the measurement result is above 65W / m·K; the mechanical strength is measured by three-point bending, and the measurement result is above 650MPa; the fracture toughness is measured by the single-side pre-crack method of ASTMC1421, and the measurement result is ≥6.0MPa·m 1 / 2 The microstructure was analyzed by SEM, which confirmed that the substrate had a uniform particle size distribution of 0.5 to 2 μm and a porosity of ≤1%.
[0032] Embodiment 2:
[0033] By adjusting the particle size range of low-cost silicon nitride raw materials and high-performance silicon nitride raw materials, the manufacturing cost can be reduced by 40%, while maintaining the thermal conductivity of the substrate to be above 65W / m·K and the strength to be above 700MPa. The purchase cost of the silicon nitride powder of the present invention is compared with the purchase cost of the silicon carbide powder of the prior art. The following is a comparison table 1:
[0034]
[0035] It can be seen that the present invention has lower cost when making a silicon nitride-based ceramic substrate and can obtain a silicon nitride-based ceramic substrate with better performance.
[0036] The performance of the silicon nitride-based ceramic substrate of the present invention is compared with the high-performance SN substrate and ZTA substrate in the prior art, as shown in Comparative Table 2:
[0037]
[0038] Compared with the existing high-performance SN substrate and ZTA substrate, the low-cost silicon nitride substrate of the present invention has the following characteristics: thermal conductivity: 65-70W / m·K, more than twice that of the existing ZTA substrate; mechanical strength: 650-700MPa, more than 25% improvement over ZTA; fracture toughness: 6.0-7.0MPa·m 1 / 2 , about 2 times better than ZTA; manufacturing cost: save 40% compared with existing high-performance SN substrates; microstructure: SEM analysis results show that the particle size distribution and porosity are similar to those of conventional high-performance substrates. These results are achieved through the mixed composition of low-cost raw materials and optimized sintering conditions, providing an economical alternative that meets market demand.
[0039] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A high-performance and low-cost silicon nitride-based ceramic substrate, comprising a low-cost silicon nitride raw material, a high-performance silicon nitride raw material, Y2O3, MgO, butyl acetate, a dispersant, and a prefabricated adhesive, characterized in that: The low-cost silicon nitride raw material has a powder particle size of 1-3 μm; the high-performance silicon nitride raw material has a powder particle size of 0.7 μm. In the low-cost silicon nitride raw material and the high-performance silicon nitride raw material, Al≤200ppm, Fe≤100ppm, and Ca≤50ppm.
2. A high-performance, low-cost silicon nitride-based ceramic substrate according to claim 1, characterized in that: The low-cost silicon nitride raw material is 50wt%; the high-performance silicon nitride raw material is 50wt%; Y2O3 is 2mol%; MgO is 5mol%; butyl acetate is 60wt% of the total amount of the low-cost silicon nitride raw material and the high-performance silicon nitride raw material; the dispersant is 0.5wt%; the prefabricated adhesive includes 70wt% of butyl acetate and 30wt% of resin mixed, and the weight percentage of the prefabricated adhesive is 10-25wt% of the total amount of the low-cost silicon nitride raw material and the high-performance silicon nitride raw material.
3. The method for manufacturing a high-performance and low-cost silicon nitride-based ceramic substrate according to claim 1, characterized in that: The steps include: S1: Raw material preparation and quality management, prepare low-cost silicon nitride raw materials, high-performance silicon nitride raw materials, Y2O3, MgO, butyl acetate, dispersant, prefabricated adhesive. The prefabricated adhesive is in a gel state with a viscosity of 30,000 cps. Test the Al, Fe, and Ca in the low-cost silicon nitride raw materials and high-performance silicon nitride raw materials. When they meet the requirements of Al≤200ppm, Fe≤100ppm, and Ca≤50ppm, they can be used; S2: Slurry preparation: low-cost silicon nitride raw material, high-performance silicon nitride raw material, Y2O3, MgO, butyl acetate, dispersant, and prefabricated adhesive are ball-milled for 10 hours using 10 mm silicon nitride balls. After the first ball-milling, they are ball-milled for 10 hours using 10 mm silicon nitride balls. After mixing, impurities are removed by a 10000 gaus magnetic filter and a 10 μm ink cartridge filter. Then, the mixture is treated with a vacuum degasser for 30 minutes to remove residual bubbles, thereby making a slurry. S3: Molding and inorganic coating: prepare a PET film, and mold the slurry into a thickness of 0.40 mm on one side of the PET film through a casting process. Cut the molded substrate into a size of 170 mm × 230 mm, and evenly coat BN on the opposite side of the PET film by spray coating, wherein the BN coating thickness is 5-10 μm, thereby completing the molded substrate; S4: heat treatment, including degreasing: the formed substrate is heated to 250°C at 5°C / min in a nitrogen atmosphere and maintained for one hour. After the temperature is maintained, the temperature is increased to 500°C at 2°C / min and maintained for 2 hours, and then the temperature is increased to 1000°C at 3°C / min and maintained for 1 hour. Sintering: The degreased substrate is kept at 1900°C for 3 hours in a sintering furnace under nitrogen pressure of 9 bar. After the holding period, it is naturally cooled to 1500°C at 9 bar and then forcedly cooled using a high-speed fan. S5: Post-processing: wet grinding of the sintered substrate to remove BN particles remaining on the substrate surface and improve the surface roughness to less than 10um; S6: Test the post-processed substrate, including thermal conductivity, mechanical strength, fracture toughness, and microstructure. The thermal conductivity is measured by the hot wire method, and the measurement result is above 65W / m·K; the mechanical strength is measured by three-point bending, and the measurement result is above 650MPa; the fracture toughness is measured by the single-side pre-crack method of ASTMC1421, and the measurement result is ≥6.0MPa·m 1 / 2 The microstructure was analyzed by SEM, which confirmed that the substrate had a uniform particle size distribution of 0.5 to 2 μm and a porosity of ≤1%.